2013
DOI: 10.1186/2051-1426-1-s1-o24
|View full text |Cite
|
Sign up to set email alerts
|

A novel peptide therapeutic targeting PD1 immune checkpoint with equipotent antagonism of both ligands and a potential for better management of immune-related adverse events

Abstract: Sasikumar et al.: A novel peptide therapeutic targeting PD1 immune checkpoint with equipotent antagonism of both ligands and a potential for better management of immune-related adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was recently reported that immune checkpoint inhibitors with a half-life of more than 15–20 days and a target binding rate of more than 70% after several months of treatment caused a series of severe side effects in clinical trials. 44 Although the mechanism has not been fully elucidated, some researchers speculated that the severe side effects may be associated with the long half-life of such drugs, suggesting that diabodies with a short half-life might decrease the risk of adverse reactions. In mouse models, no obvious difference was observed between the diabody-treated groups and the control group in terms of activity, weight, and eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that immune checkpoint inhibitors with a half-life of more than 15–20 days and a target binding rate of more than 70% after several months of treatment caused a series of severe side effects in clinical trials. 44 Although the mechanism has not been fully elucidated, some researchers speculated that the severe side effects may be associated with the long half-life of such drugs, suggesting that diabodies with a short half-life might decrease the risk of adverse reactions. In mouse models, no obvious difference was observed between the diabody-treated groups and the control group in terms of activity, weight, and eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…AUNP‐12 has been proven to perform well on the antagonism of PD‐1 by subcutaneous administration and showed a safe toxicological profile. [ 77 ] Although peptide antagonists have better tumor penetration properties, short‐term retention in tumor tissues limits their application. Therefore, the authors applied subcutaneous injection of AUNP‐12‐loaded phospholipid‐based phase separation gel (PPSG) near the tumor to achieve long‐term sustained release of the antagonist.…”
Section: Strategies Of Bacteria‐based Cancer Immunotherapymentioning
confidence: 99%
“…Unfortunately, despite impressive clinical activity, severe immune‐related adverse events (irAEs) due to the disruption of immune self‐tolerance have become evident in certain cases. Sustained target inhibition as a result of a long half‐life and strong target occupancy for months likely contribute to the irAEs observed in the clinic with antibodies against immune checkpoint proteins …”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%